The Relationship Between Agility and Speed on Futsal Dribbling - Setyawan, Dicky Budhi; Peking, Intan Marchelina (S&Co Publishing, 2023)
The purpose of this study was to obtain data on agility and speed on the ability to dribble futsal extracurricular futsal students at SMP PGRI 12 Cilandak. This research uses a quantitative approach to correlational techniques. The study population was futsal extracurricular students at SMP PGRI 12 Cilandak with a sample of 30 students obtained through random sampling technique.The results showed that there was a positive effect of agility on dribbling, positive effect of speed on dribbling. Agility and speed had a very strong relationship and indicating that it has a significant influence on dribbling. In futsal training, agility and speed can be implemented to enhance dribbling ability.